Interleukin-4 and Interleukin-13 Gene Polymorphisms in Children With Idiopathic Nephrotic Syndrome - Al Rushood, Maysoun; Al-Eisa, Amal A.; Haider, Mohammad Z. (Frontiers in Pediatrics, 2020)
Background: Idiopathic Nephrotic syndrome (INS) is an immune-mediated disease in which a num-ber of cytokines, including IL-4 and IL-13, have been implicated in the pathogenesis. Cytokine gene polymorphisms might affect their levels and activity. Therefore, may affect INS susceptibility and re-sponse to treatment. The aim of the study was to determine the association of IL-4 and IL-13 gene polymorphisms and INS susceptibility and their effects on steroid responsiveness in children. Methods: The polymorphisms in IL-4 and IL-13 genes were detected by PCR-RFLP in 155 INS pa-tients and 64 controls. Results: A total of 132 steroid-sensitive (SS) and 23 steroid resistance (SR) INS patients; mean age 7.3±4.0 years, were included. Male: Female ratio was 2:1. No significant statistical differences were detected in the frequency of CC, CT and TT genotypes of IL-4 gene compared to controls (P=0.57, 0.61 and 1.00, respectively). There was no significant difference in the T and C-allele frequencies, in SS and SR subgroups. Analysis of IL-13 gene polymorphism also did not show significant statistical differences in the frequency of QQ, RQ and RR genotypes compared to controls (P=0.74, 1.00 and 0.68, respectively). No significant difference was found in the Q and R-allele frequency. However, the heterozygous RQ genotype of the IL13 gene was significantly higher in SS INS patients com-pared to the SR INS cases (P =0.04). Conclusion: Our findings from did not show an association between IL-4 and IL-13 gene polymor-phisms and INS susceptibility. However,IL-13 RQ genotype was expressed more in children with INS who are steroid sensitive.